Effect of organic modifier type of montmorillonite on the poly (butyl acrylate-co-methyl methacrylate)/montmorillonite nanocomposite - Vatansever, Alican; Inan, Tulay; Dogan, Hacer; Sirkecioglu, Ahmet (Springer Science and Business Media LLC, 2015)
Nanocomposites based on poly(BA-co-MMA) and organo-montmorillonite (OMt) were synthesized by semi batch emulsion polymerization. OMt was used directly after the organic modification of sodium montmorillonite (Mt). By this way, dispersion of OMt in emulsion polymerization was improved. OMts were prepared by organic modification of Resadiye Mt (bentonite) with five different quaternary ammonium salts (QAS) to observe the effect of structural difference on the poly(butyl acrylate-co-methyl methacrylate) nanocomposites. The affinity of OMts towards organic liquids was observed via swelling test in toluene and butyl acrylate (BA)-methyl methacrylate (MMA) mixture. OMt content in the nanocomposite as well as the effect of QAS structure and dosage was investigated. Good dispersion of OMt in copolymer films was obtained as demonstrated by X-ray diffraction and partially exfoliated OMt structure was determined through transmission electron microscope. Final nanocomposites had 47 wt% solids contents. Nanocomposite containing 2.3 wt% OMt modified with two 18 carbons alkyl chain at excess QAS amount resulted in higher increments of thermal, mechanical, barrier properties and glossiness for coating applications.